QARAQALPAQ TIL BILIMINDE NAQÍL-MAQALLARDÍŃ JÍYNALÍWÍ HÁM IZERTLENIW TARIYXÍ - Sailaubaeva, Gozzal Azatovna (SCIENCE and SOCIETY, 2026)
This article comprehensively examines the history of collecting and studying Karakalpak proverbs in Karakalpak linguistics. It analyzes the stages of collecting proverbs as folklore materials and highlights the scholarly contributions of both foreign and local researchers to their collection, systematization, and investigation. Particular attention is paid to literary, linguistic, lexical-semantic, phraseological, paremiological, and linguocultural approaches to the study of Karakalpak proverbs. The paper emphasizes the significance of the works of T.Niyetullaev, Kh.Oteniyazova, B. Yusupova, and other scholars in the development of Karakalpak paremiology. Furthermore, it discusses the importance of applying modern linguistic methods to the study of proverbs and outlines promising directions for future research.